Article on: “Evaluation of Factors Causing Cost Variation in Construction of Water Supply Projects in Nepal” - Khadka, Suman (Mid-West University Journal of Engineering & Innovation, 2025)
Cost is one of the major considerations throughout the project management life cycle and can be regarded as one of the most important parameters of a project and the driving force of project success. Despite its proven importance, it is common to see a construction project failing to achieve its objectives within the specific cost. Cost variation is a very frequent phenomenon and is almost associated with nearly constructing all water supply projects. Maintaining steady cost projection on water supply projects had been recently an issue of serious concern, both to the client and contractors. This research work attempts to identify, investigate and rank factors supposed to affect cost variation in the Nepalese water supply construction projects with respect to their relative importance so as to proffer possible ways of deal with this occurrence.To achieve this objective, the study uses a mixed-method approach, including a structured questionnaire survey and research papers, to gather data. Brain storming was taken into consideration, through which a number of cost variation factors were identified for constructing water supply projects. Totally 25 factors were short-listed to be made part of the questionnaire survey and the survey was conducted with experts, consultants, employers and contractors‟ representatives. The study further utilizes the Relative Importance Index (RII) to rank factors causing cost variations. It was analytically discovered that several key factors such as: (1) Mistake and errors in design, drawing, estimation and BoQ (2) Change in project design and scope (3) Due to change in scope and additional work (4) Inappropriate preconstruction study and project analysis and (5) Design not finalized before tendering were critical for causing cost variation for the construction for water supply projects, while (1) Domination of construction industry by foreign firms and aids (2) Unavailability of construction materials (3) By selecting lowest bidding procurement method (4) Financing mode and payment difficulties for completed work (5) Involvement of more number of parties in a single project are least responsible factor causing cost variation. The study concluded with recommending implement comprehensive and detailed design and review processes, enhance preconstruction site investigations and proper feasibility studies, introduce stricter project scope control mechanisms and improve client’s project management procedures, apply advanced design, cost estimation and project management mechanism and software while designer should be aware of the site problems, strengthen stakeholder engagement and dispute resolution mechanisms, conduct regular capacity building training for staffs on accurate project cost control, planning and risk management in water supply projects for smoother implementation and achievement of desired cost control.